Integration of a StatCom and battery energy storage. - Yang, Z. (IEEE Transactions on power systems)
The integration of an energy storage system, such as battery energy storage (BESS), into a FACTS device can provide dynamic decentralized active power capabilities and much needed flexibility for mitigating transmission level power flow problems. This paper introduces an integrated StatCom/BESS for the improvement of dynamic and transient stability and transmission capability; compares the performance of the different FACTS/BESS combinations, and provides experimental verification of the proposed controls on a scaled StatCom/BESS system